2019
DOI: 10.1507/endocrj.ej18-0467
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid promotes browning of white adipose tissues in high-fat diet-induced obesity in rats through suppressing white adipocyte maintaining genes

Abstract: Promoting brown adipose tissue (BAT) formation and function reduces obesity. Ellagic Acid (EA), located abundantly in plant extracts and fruits, has been shown to modulate formation and differentiation of adipocytes, although its role in the process of browning of white adipose tissue (WAT) has not been elucidated. In this study, fifty-six five-week old SD rats were randomly assigned to receive normal diet (ND, 10% lipids) or high-fat diet (HFD, 60% lipid) with or without various dosages of EA for 24 weeks. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…Thus, compounds inducing UCP1 in WAT may be useful therapeutic agents for the treatment of obesity. Interestingly, the administration of ellagic acid to cold-exposed mice and HFD-fed mice induced the browning of WAT, as confirmed by the increase in UCP1 expression [52,53]. In the present study, we confirmed that an intake of 5-uRCK and its main active compound ellagic acid reduced the size of adipocytes and enhanced the production of UCP1 and PGC1α in subcutaneous ingWAT by immunoblot analyses.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, compounds inducing UCP1 in WAT may be useful therapeutic agents for the treatment of obesity. Interestingly, the administration of ellagic acid to cold-exposed mice and HFD-fed mice induced the browning of WAT, as confirmed by the increase in UCP1 expression [52,53]. In the present study, we confirmed that an intake of 5-uRCK and its main active compound ellagic acid reduced the size of adipocytes and enhanced the production of UCP1 and PGC1α in subcutaneous ingWAT by immunoblot analyses.…”
Section: Discussionsupporting
confidence: 83%
“…Porcine beige adipogenesis-related DEGs were screened, and the pathways of brown fat differentiation and oxidative phosphorylation were found to be enriched. Consistently, previously defined BAT/beige adipocyte markers in humans and rodents, including EBF2 [ 29 ], TNF receptor superfamily member 9 (CD137) [ 8 , 30 ], mitochondrial transcription factor A (TFAM) [ 31 , 32 ], PPARG coactivator 1 alpha (PPARGC1A) [ 33 ], type 2 iodothyronine deiodinase (DIO2) [ 34 , 35 ], and potassium channel K3 (KCNK3) [ 10 ], were indeed specifically upregulated in porcine beige adipocytes. Therefore, these well-known thermogenic genes in humans and rodents can unambiguously evaluate the thermogenic capacity of porcine adipocytes.…”
Section: Discussionsupporting
confidence: 62%
“…While the loss of ALDHs coincides with complete loss of glucose utilization in both KO clones, the causal effect, if any, between these two events will need further investigation. Future studies will be needed to confirm if LDHA/B inhibitors could be combined with ALDH inhibitors to evoke a more significant chemotherapeutic effect of drugs and radiation (48), and could be explored with ALDH inhibitors such as (-)epigallocatechin gallate (65,66), rocaglamide A (67), NCT-501 (67), and ellagic acid (68).…”
Section: Reduction In Aldehyde Dehydrogenase Transcripts (Aldhs)mentioning
confidence: 99%